Histological Scoring for Nonalcoholic Fatty Liver Disease A Study in 55 Cases - Khanam, Rehana; Kamal, Muhammad; Jahan, Fauzia; Ghosh, P. K. (Journal of Medicine, 2014)
Background: Steatohepatitis is a pattern of liver injury that may be seen in alcoholic or nonalcoholic liver disease. This morphological changes may occur with obesity, diabetes, the use of certain drugs or it may be idiopathic. The main histopathological features of nonalcoholic steatohepatitis (NASH) include hepatocellular steatosis and ballooning, mixed acute and chronic lobular inflammation and fibrosis. The recently developed histological scoring system for NAFLD by the NASH Clinical Research Network (NASH CRN) is becoming increasingly popular. The purpose of this study was to develop grading andstaging system and was based on liver biopsies from 50 patients with Nonalcoholic Steatohepatitis from BSMMU and other clinics of Dhaka city. Objective: This study was done to analyze the histological spectrum and to develop grading and staging system in patients with nonalcoholic fatty liver disease. Methods: This cross sectional study was carried out at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. A total of 55 patients with non-alcoholic fatty liver disease (NAFLD) who fulfilled the inclusion criteria were selected for the study. Liver biopsy was done at hepatology department of BSMMU, and different clinics of the Dhaka City from july 2006 to june 2007. The data of patients along with histopathological reports were studied. Results: Out of total 55 cases of Nonalcoholic Fatty Liver Disease 33 were male (63.63%) and 22 were female (40%). Mean age of the patient was 37.81±10.80 years. 35 (63.63%) patients were obese. 2 patients (3.63%) were diabetic. Among 55 patients NAFL (steatosis) were diagnosed in 6 patients (10.90%) and NASH in 49 patients (89.09%). Forty two (16.36%) of the 46 Definite NASH biopsy specimen exhibited fibrosis and three had cirrhosis. DOI: http://dx.doi.org/10.3329/jom.v14i2.19638 J Medicine 2013, 14(2): 114-118